FORMULATION and ANTI BURN ACTIVITY SPRAY GEL OF SENGGANI LEAF EXTRACT (Melastoma malabathricum L.) - Fitriani, Eka; Wijaya, Mario; Pratiwi, Galih; Tari, Mayang; Alta, Ulik; Indriani, Onny (Jurnal Farmasi Klinik dan Sains, 2024)
Senggani leaves contain quercetin, which is a flavonol, one of the six subclasses of flavonoid compounds and has many pharmacological effects such as antioxidant, anti-inflammatory and anti-diabetic, able to speed up the healing process of burn wounds. Spray gel for topical treatment of burns used on the skin has advantages, including being safer because the level of microorganism contamination is lower. The aim of the research is to formulate and determine the effectiveness of a spray gel preparation of senggani leaf extract (Melastoma malabathricum L.) against burns. This research is experimental research. The making of senggani leaf extract spray gel uses carbopol 940 and HPMC as gelling agents. The selected formula is then tested for its effectiveness against burns. Data analysis used the oneway anova test and the Duncan test. Results: Spray gel formula with selected senggani leaf extract based on carbopol 0.5 g, HPMC 2 g. The results of statistical analysis in the anti-burn activity test showed a significant difference between the senggani leaf extract spray gel group and the positive control. Senggani leaf extract gel spray provides better effectiveness than the positive control in the burn wound healing process